Individual, family and offence characteristics of high risk childhood offenders: comparing non-offending, one-time offending and re-offending Dutch-Moroccan migrant children in the Netherlands - Stevens Gonneke WJM; van Domburgh Lieke; Paalman Carmen H; Doreleijers Theo AH (BMC, 2011)
Abstract Background Childhood offenders are at an increased risk for developing mental health, social and educational problems later in life. An early onset of offending is a strong predictor for future persistent offending. Childhood offenders from ethnic minority groups are a vulnerable at-risk group. However, up until now, no studies have focused on them. Aims To investigate which risk factors are associated with (re-)offending of childhood offenders from an ethnic minority. Method Dutch-Moroccan boys, who were registered by the police in the year 2006-2007, and their parents as well as a control group (n = 40) were interviewed regarding their individual and family characteristics. Two years later a follow-up analysis of police data was conducted to identify one-time offenders (n = 65) and re-offenders (n = 35). Results All groups, including the controls, showed substantial problems. Single parenthood (OR 6.0) and financial problems (OR 3.9) distinguished one-time offenders from controls. Reading problems (OR 3.8), having an older brother (OR 5.5) and a parent having Dutch friends (OR 4.3) distinguished re-offenders from one-time offenders. First offence characteristics were not predictive for re-offending. The control group reported high levels of emotional problems (33.3%). Parents reported not needing help for their children but half of the re-offender's families were known to the Child Welfare Agency, mostly in a juridical framework. Conclusion The Moroccan subgroup of childhood offenders has substantial problems that might hamper healthy development. Interventions should focus on reaching these families tailored to their needs and expectations using a multi-system approach.